Penerapan Model Pembelajaran Flipped Classroom dengan Integrasi Diferensiasi Produk untuk Meningkatkan Aktivitas dan Hasil Belajar Ekonomi Siswa Kelas XII IPS 1 SMA Negeri 2 Busungbiu - Putu Agus Eka Sedana Jaya (Ekuitas: Jurnal Pendidikan Ekonomi, 2023)
The classroom based researh aimed at discovering the aplication of Filpped Classroom learning model with the integration of product differentiation to improve the activity and the result study of Economy subject. This reserch was done into two cycles, where every cycle consisted of  planning phase, implementation, observation, evaluation, and reflection. The subject of the research were the students of second semester of XII IPS 1 SMA Negeri 2 Busungbiu in the academic year of 2021/2022 which consists of 27 students. The object of the research was the improvement of the activity and the result study of in economy subject by the aplication of flipped classroom learning model integrated with product differentiontion. The data of the activity and the result study was collected by using observation method, questionairre, and test. The result of the research shows that there was an improvement of the activity and the result study from cycle I by the average 2,07 which can be categorized pretty good  to be 2,56 which are good in cycle II. In the result study of Economy subject, students also had an improvement by the whole average  67,41, the retention was 67,41%, and the classical completion 70,37% in cycle I to be 75,56 in average, the retention was 75,56% and the clasical completion  is 85,19% in cycle II. Based on the result of the research, it can be concluded that the aplication to the flipped classroom learning model with the integration of product diferentiation can improve the learning activity and the result study of economy subject.